Cross-Sectional analysis of demographic and clinical characteristics of patients in the United States using icosapent ethyl - Toth, Peter P.; Nelson, John R.; Soran, Handrean; Ganda, Om P.; Wong, Nathan D.; Hannachi, Hakima; Abrahamson, David; Hartman, Josh; Luciano, Sierra; Philip, Sephy (Frontiers in Cardiovascular Medicine, 2025)
IntroductionIcosapent ethyl (IPE) is indicated for the treatment of severe hypertriglyceridemia (triglycerides ≥500 mg/dl) and for reducing the risk of cardiovascular (CV) events in statin-treated adults with moderately elevated triglycerides (150–499 mg/dl) and established CV disease [secondary prevention (SP)] or diabetes with CV risk factors [primary prevention (PP)]. We describe real-world characteristics of US patients taking IPE.MethodsPatients with ≥2 IPE prescriptions were identified in the TriNetX database. PP criteria were: ≥50 years with diabetes mellitus, ≥1 additional CV risk factor, and triglycerides 150–499 mg/dl. SP criteria were established CV disease and triglycerides 150–499 mg/dl.ResultsAmong patients with ≥2 IPE prescriptions and triglyceride data, 56.2% (18,897/33,645) met PP or SP criteria, 28.0% (9,431/33,645) had severe hypertriglyceridemia. In the PP and SP cohorts, mean (SD) ages were 62.7 (8.0) and 64.0 (10.7) years, respectively. In the SP cohort, coronary artery disease was the most common pre-existing CV disease (85.8%) and many had diabetes (63.1%). In the PP and SP cohorts, 81.7% and 90.4%, respectively, received statin treatment. Before IPE initiation, mean (SD; median) triglyceride levels were 305 (150; 253) and 279 (142; 230) mg/dl in the PP and SP cohorts, respectively, and mean/median LDL-C levels were <100 mg/dl in both.DiscussionPatients taking IPE had characteristics consistent with its indication, including well-controlled LDL-C levels with statin use. The higher triglyceride levels before IPE initiation suggest that IPE may be underutilized in patients at high risk for CV events; however, future studies are needed.